Syphilis as Rare Cause of Pyogenic Liver Abscess - Danielle Meyer; Michele Granada (Emerging Infectious Diseases)
Syphilis has a wide range of possible symptoms, making it difficult to diagnose. We report a rare case of liver abscess secondary to Treponema pallidum in a man in Minnesota, USA, who had well-controlled HIV infection. This case emphasizes the importance of appropriate screening for syphilis, especially in high-risk populations.